Antibiotic prescribing for acute lower respiratory tract infections (LRTI) - guideline adherence in the German primary care setting: an analysis of routine data - Kraus, Eva Maria; Szecsenyi, Joachim; Laux, Gunter (PLOS ONE, 2017)
Objectives Antibiotic overprescribing in primary care has major impacts on the development of antibiotic resistance. The objective of this study is to provide insight in antibiotics prescriptions for patients suffering from cough, acute bronchitis or community acquired pneumonia in primary care. Methods Data from 2009 to 2013 of electronic health records of 12,880 patients in Germany were obtained from a research database. The prescription of antibiotics for acute lower respiratory tract infections was compared to the national S3 guideline cough from the German Society of General Practitioners and Family Medicine. Results Antibiotics were prescribed in 41% of consultations. General practitioners’ decision of whether or not to prescribe an antibiotic was congruent with the guideline in 52% of consultations and the antibiotic choice congruence was 51% of antibiotic prescriptions. Hence, a congruent prescribing decision and a prescription of recommendation was found in only 25% of antibiotic prescriptions. Split by diagnosis we found that around three quarters of antibiotics prescribed for cough (73%) and acute bronchitis (78%) were not congruent to the guidelines. In contrast to that around one quarter of antibiotics prescribed for community acquired pneumonia (28%) were not congruent to the guidelines. Conclusions Our results show that there is a big gap between guideline recommendation and actual prescribing, in the decision to prescribe and the choice of antibiotic agent. This gap could be closed by periodic quality circles on antibiotic prescribing for GPs.